Is it really unreal? A two-theory approach on the impact of deepfakes technology on the protection motivation of consumers - Dhanya Pramod; Kanchan Pranay Patil; Vijayakumar Bharathi S (Cogent Business & Management)
This study examined the impact of deepfakes on consumer protection behaviour and psychosocial responses, focusing on threats and coping appraisals in deepfake marketing. The study applied a two-theory framework combining the Theory of Planned Behavior and the Protection Motivation Theory. Data from 317 adult consumers were collected using a structured questionnaire. Scales were adapted from prior research, and analysis was conducted using Partial Least Squares Structural Equation Modeling (Smart-PLS 4.0 software). The results revealed that threats, attitudes, and subjective norms significantly influenced protective behaviour, while perceived behavioural control did not. Perceived severity and susceptibility significantly affected attitude and motivation to comply impacted consumers’ subjective norms. Perceived Response Efficacy, Self-Efficacy, and Perceived Response Cost were not supported as drivers of perceived behavioural control. This research on consumers’ threat and coping appraisals of deepfake technology offers key insights. It advances consumer behaviour theories in information systems, aids stakeholders like companies and marketers, and supports policymakers in developing regulations and safeguards against deepfake threats.